Evolution in key indicators of maternal and child health across the wealth gradient in 41 Sub-Saharan African countries, 1986–2019 - Sesabo, Jennifer K. (BMC Medicine, 2024)
This article submitted to the BMC Medicine Article, Vol. 22. No. 21of 2024.